Evaluating Program Impact on Resilience: Evidence from Lesotho's Child Grants Programme. Issue 12 (1st December 2020) - d'Errico, Marco; Garbero, Alessandra; Letta, Marco; Winters, Paul
Abstract: Social protection programmes can play a crucial role in enhancing household resilience. Although there is vast evidence on the impact of cash transfer projects on many welfare outcomes, no study examines the impact of cash transfers on a composite measure of resilience. This paper fills this important gap by employing a difference-in-difference estimator in the context of a randomised control trial in Lesotho to explore the causal effect of a Child Grant Programme on resilience capacity. Results show a positive and significant short-term impact, largely driven by the beneficial effects for less resilient households. The main transmission channels are increases in household expenditure and food security. Strong stimulus of the Programme on expenditure in education, a key resilience determinant, anticipates longer-run virtuous intergenerational dynamics in resilience building. The policy implication of this work is that social protection interventions should be embedded within the larger framework of resilience-enhancing programmes.